Card-sales response to merchant contactless payment acceptance - Bounie, David; Camara, Youssouf (Journal of Banking & Finance, 2020)
Disruptive innovations in digital payments are happening in a large number of countries around the world. In this paper, we investigate how merchants’ acceptance of a contactless card technology affects card sales. Using score matching and difference-in-difference techniques on a unique sample of about 275,580 merchants in France, we find that accepting contactless payments in 2018 increases the card-sales amount by 15.3 percent on average (and by 17.1 percent the card-sales count) compared to merchants who do not accept contactless payments. We also find evidence that accepting contactless payments exerts a positive spillover of about 1.3 percent in the amount of contact card sales, and thus significantly increases the average annual card-sales amount and count for small merchants and new entrepreneurs.